A Confederate chronicle the life of a Civil War survivor - Hain, Pamela Chase, 1936- (Shades of blue and gray series., 2005)
"Focuses on the struggles of Civil War veteran Thomas L. Wragg, Confederate officer, prisoner of war, and successful doctor. Documents General Joseph E. Johnston's army at Harpers Ferry and the Battle of Bull Run, Wragg's training on the CSS Georgia, his imprisonment, his courtship, and the effects of posttraumatic stress"--Provided by publisher.